Physical layer security for visible light communication systems subject to eavesdropper location uncertainty - Cho, S (2020)
The past few decades have witnessed the acceleration in the development of groundbreaking information technology applications, such as smartphones/tablets, Internet of Things devices, virtual reality devices, etc. These new applications require a significant amount of data traffic to be conveyed wirelessly. Furthermore, the growing number of devices imposes a big challenge of providing seamless and low-delay communication. To satisfy these requirements, visible light communication (VLC) systems have gained considerable popularity thanks to its inherent advantages, such as unlicensed wide bandwidth, high area spectral efficiency, and high security. At the same time, in VLC systems, network security remains a significant challenge. Even with the inherent wireless communication security of VLC systems, there is still a possibility that an eavesdropper can wiretap important/private information in large open spaces. Therefore, this research investigates physical layer security (PLS) to secure the VLC indoor transmission in the presence of randomly located eavesdroppers, proposing three different beamforming and jamming strategies for different VLC system scenarios. PLS is a set of techniques that enable a transmitter and a legitimate receiver to securely transmit and receive important data, eliminating the possibility of eavesdropping by utilizing the randomness of a channel between transmitter and receiver. Dealing with the random locations of eavesdroppers by using tools from stochastic geometry, the proposed PLS schemes do not require precise locations or channel state information of eavesdroppers. Numerical and Monte Carlo simulation results are provided to verify the performances of the proposed schemes.